Analysing university students' abilities in making assumptions in a ballistics model: a case study - Klymchuk, S (The Bronx Colleges of the City University of New York, 2016)
This paper investigates abilities of two groups of university students in making assumptions in a ballistics model. The first group consisted of postgraduate students majoring in applied mathematics from a New Zealand university and the second group consisted of first-year science students majoring in applied mathematics from an Australian university. The students were asked to make reasonable assumptions in a ballistics model from mechanics. We started talking about stones thrown by catapults in ancient times and proceeded to discussing firing balls from cannons in medieval times and launching projectiles and missiles in recent history. Students’ responses to the questionnaire on assumptions are presented and analysed in the paper.